Learners’ ideal L2 self and self-perceived communicative competence - Septi Subekti, Adaninggar (Vestnik za tuje jezike, 2025)
Despite the growing popularity of the Indonesian language among non-Indonesians and the abundance of research on individual differences in second/foreign language (L2) learning, there is a scarcity of studies investigating the role of individual difference factors among learners of BIPA (Indonesian Language for Foreign Speakers). The present study intends to examine BIPA learners’ Ideal L2 Self (IL2S) and Self-Perceived Communicative Competence (SPCC) in the Indonesian language. It also seeks to investigate how the learners’ IL2S influenced their SPCC. To achieve this, the study examined a group of BIPA learners from China. Using a survey method with paper-based questionnaires, this study found that the participants reported high levels of both IL2S and SPCC. The high IL2S level could be attributed to the possibility that these learners were high-achieving, considering they had been shortlisted for a BIPA programme in Indonesia, and that they perceived Indonesian as a relatively easy language to learn. The high SPCC level may be attributed to the learners’ having specific goals in learning the language and to the Indonesian language exposure they gained during their immersive BIPA programme. This study also found that the participants’ IL2S significantly predicted their SPCC, explaining 42.8% of the total variance in their SPCC. The pedagogical implications include enhancing the relevance of BIPA courses to aid the development of learners’ IL2S, which may lead to a more positive perception of communicative competence in the language. This study could provide an overview of BIPA learners’ IL2S and SPCC. It may prepare the ground for further relevant studies on the roles of these two affective factors in the L2 learning of the Indonesian language.
Keywords: BIPA (Indonesian Language for Foreign/non-Indonesian Speakers); BIPA (indonezijski jezik za tuje/neindonezijske govorce); dojemanje lastnih komunikacijskih kompetenc (DLKK); drugi jezik (J2); Ideal L2 Self (IL2S); idealni jaz v drugem jeziku (IJJ2); second language (L2(; Self-Perceived Communicative Competence (SPCC)